Assessing London International Financial Center in Double Uncertain Scenarios - Dai Thich Phan (Studies in Business and Economics, 2022)
Most economies in the world have been isolated from the global by regulations in the prevention of covid 19, and the international trading activities are greatly affected that then affects financial services activities in major financial centers around the world. The situation of London IFC is quite different from others because of the covid 19 pandemics and the negotiation process of Brexit, which makes London IFC in a period of double uncertainty. This paper set out to investigate some effects of double scenarios of the Covid-19 pandemic and Brexit on the London IFC. The research will highlight some variations in payment activities, employment, the trading value in the financial and insurance sectors, foreign market activities, and fintech sectors in London.